(untitled) (Journal of Atomic and Molecular Sciences, 2012)
The gas phase reaction between dimethylsulfide (DMSO) and hydroxyl radical (OH) without and with a single water molecule are investigated employing the quantum chemical calculations at the b3lyp/aug-cc-pvtz and mp2/aug-cc-pvtz levels of theory, respectively. We have been given five paths of OH radical with DMSO (A , B, C, D and E). The geometries and computed energies not only indicate that water molecule produces a catalytic effect for path A and path B, but produces a negative effect for path C, path D and path E. We also give the rate constants to support the above result. We can draw the conclusion that water molecule can influence the reaction process, through forming new molecular compounds.